IMPLEMENTATION OF DEEP LEARNING IN IMPROVING STUDENTS’ CRITICAL THINKING SKILLS IN SCIENCE LEARNING IN ELEMENTARY SCHOOLS - Noptario, Noptario; Rizky, Nikentari; Irawan, M. Ferry; Putri, Nadya Syafira (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2026)
This study aims to disseminate the effect of the implementation of the deep learning model on improving students’ critical thinking skills in learning Natural and Social Sciences (IPAS) in elementary schools. The study used a quantitative approach with a quasi-experimental design of the non-equivalent control group design, involving two fifth grade classes at Margoluwih Public Elementary School, Sleman, each consisting of 26 students as the experimental group and 26 as the control group. The research instrument was a critical thinking test consisting of 10 essay questions that measured four indicators of critical thinking skills, namely telling stories, expressing ideas, concluding, and providing logical reasons. Data were analyzed using an independent t-test with the help of SPSS software. The results of the study showed that there was a significant difference between the average posttest results of students in the experimental class and the control class with a t-value of 5.842 and a p-value of 0.000 < 0.05. The average posttest score of the experimental class was 84.35, higher than the control class of 74.04, with an effect size (Cohen’s d) of 1.75, indicating a very large effect. These findings indicate that in-depth learning can significantly improve students’ critical thinking skills through meaningful exploration, reflection, and collaborative discussion activities. Thus, the application of in-depth learning can be an alternative effective learning strategy to develop high-level thinking skills in elementary school students, especially in science learning that requires the integration of scientific and social knowledge.